2022
DOI: 10.1088/1361-6463/ac6637
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of F-containing species in atmospheric nanosecond He/CF4 plasma with downstream dielectric material

Abstract: A two dimensional self-consistent model has been established in order to investigate the distribution of F-containing species in He/CF4 APPJ and the effect of CF4 concentration on the reactive F-containing species. A portion of electron energy is consumed whenever an F is ionized from the CF4, resulting that the average densities of CF4+, CF2+ and CF+ decrease sequentially. The density of CF3+ is greater than CF4+ density due to Penning ionization of He* with CF4 and He+ + CF4 → CF3+ + F + He. In the case of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The mechanism of modification has not yet reached a unified understanding. To make up for the quantitative observation, numerical approaches are adopted to research the plasma-surface interaction (PSI) process between APPJ and surface under the excitation of the pulsed voltage [20,[26][27][28][29]. While obtaining the distribution of ions in a fluorocarbon plasma and giving a parametric control method, the simulation model does not adequately characterize the ions interacting with surfaces in PSI.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of modification has not yet reached a unified understanding. To make up for the quantitative observation, numerical approaches are adopted to research the plasma-surface interaction (PSI) process between APPJ and surface under the excitation of the pulsed voltage [20,[26][27][28][29]. While obtaining the distribution of ions in a fluorocarbon plasma and giving a parametric control method, the simulation model does not adequately characterize the ions interacting with surfaces in PSI.…”
Section: Introductionmentioning
confidence: 99%
“…They determined the main negative ion species and ionization mechanism in the reaction process. In our previous work [43][44][45], the effect of CF 4 ratio on APPJ with downstream dielectric material was researched, the effect of small amount of CF 4 addition on He/Ar APPJ was compared, the differences between the discharge dynamics of He/Ar + CF 4 APPJ were investigated and the effect of the relative permittivity of the downstream dielectric material on plasma-surface interaction was studied. It was found that the introduction of small amount of CF 4 would enhance the jet strength of He APPJ while significantly reduce the jet strength of Ar APPJ.…”
Section: Introductionmentioning
confidence: 99%